(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the article current state of Kazakhstan youth and the some issues of youth policy are considered. Also, different approaches of solving mentioned issues are studied. The places and roles of Public institutions, among which political parties in realizing of youth policy are defi ned. Authors analyze the main tendencies of youth policy in the country. Is was revealed that there are some youth groups threatening the society. Keywords: youth, politics, social growth, political socialization, state youth policy.